The Parallel Architecture—application and explanatory power for neurolinguistic research - Breuer, Esther Odilia; Binkofski, Ferdinand Christoph; Pellicano, Antonello (Frontiers in Language Sciences, 2025)
Various linguistic models have been developed to systematize language processes and provide a structured framework for understanding the complex network of language production and reception. However, these models have often been developed in isolation from neurolinguistic research, which continues to provide new insights into the mental processes involved in language production and comprehension. Conversely, neurolinguists often neglect the potential benefits of incorporating contemporary linguistic models into their research, although these models could help interpret specific findings and make complex concepts more accessible to readers. This paper evaluates the utility of Jackendoff's Parallel Architecture as a generic framework for explaining language acquisition. It also explores the potential for incorporating neurolinguistic findings by mapping its components onto specific neural structures, functions, and processes within the brain. To this end, we reviewed findings from a range of neurolinguistic studies on language acquisition and tested how their results could be represented using the Parallel Architecture. Our results indicate that the framework is generally well-suited to illustrate many language processes and to explain how language systems are built. However, to increase its explanatory power, it would be beneficial to add other linguistic and non-linguistic structures, or to signal that there is the option of adding such structures (e.g., prosody or pragmatics) for explaining the processes of initiating language acquisition or non-typical language acquisition. It is also possible to focus on fewer structures to show very specific interactions or zoom in on chosen structures and substructures to outline processes in more detail. Since the Parallel Architecture is a framework of linguistic structures for modeling language processes rather than a model of specific linguistic processes per se, it is open to new connections and elements, and therefore open to adaptations and extensions as indicated by new findings in neuro- or psycholinguistics.